2007
DOI: 10.1590/s0102-77862007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Distúrbios ondulatórios de leste (DOLs) na região do centro de lançamento de Alcântara-MA

Abstract: Neste artigo foi realizada uma climatologia dos Distúrbios Ondulatórios de Leste (DOLs) que passaram pela região de Alcântara-MA, no período de 1988 a 1997, utilizando-se de um método baseado na mudança do sinal da componente meridional do vento (V). Este método foi aplicado para 3 camadas distintas (entre 850 a 700 hPa, entre 700 e 500 hPa e entre 850 a 500 hPa), objetivando identificar a camada que melhor indicasse a ocorrência dos DOLs. Após a identificação dos eventos de DOLs, estes foram confirmados por u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 4 publications
0
8
0
6
Order By: Relevance
“…The dashed lines show the approximate trough axes. On day −2 d, at 1000 hPa (Figure 2 The study of [26] identified the layer with highest occurrence of EWDs throughout the entire year. Their results showed that the highest frequency of EWDs occurs in the 850-700 hPa layer during the rainy season, in accordance with the results presented here.…”
Section: Synoptic and Dynamic Analysis Of Ewdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dashed lines show the approximate trough axes. On day −2 d, at 1000 hPa (Figure 2 The study of [26] identified the layer with highest occurrence of EWDs throughout the entire year. Their results showed that the highest frequency of EWDs occurs in the 850-700 hPa layer during the rainy season, in accordance with the results presented here.…”
Section: Synoptic and Dynamic Analysis Of Ewdsmentioning
confidence: 99%
“…Several studies have shown that EWDs occur in various tropical regions, mainly in the western Pacific Ocean, Caribbean Sea, West Africa, and eastern Atlantic Ocean [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In the South Atlantic tropical region, near the Brazilian cost, EWDs can also occur, though less frequently than elsewhere [8,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, when the ITCZ shifts to its southernmost position, it is responsible for increased rainfall totals in March and April (Uvo, ; Silva, ; Utida et al ., ). In the transition between the first and second halves of the year, easterly wave disturbances (EWD) formed in the atmospheric pressure field propagate westbound from the African continent until the eastern portion of South America, influencing rainfall rates over these capitals (Dunn, ; Yamazaki, ; Coutinho and Fisch, ). Furthermore, these cities are also influenced by sea‐breeze circulation, which transport clouds from the ocean to the land, and by cold fronts propagated throughout the coastline (Rotunno, ; Sousa et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Diversos estudos sobre as características turbulentas do local já foram realizadas, quer seja por observações (Fisch, 1999e Roballo e Fisch, 2008, quer seja por ensaios em túnel de vento (Pires et al, 2009). Também já foram realizados estudos sobre a atuação de sistemas atmosféricos no local (Barbosa et al, 2006, Coutinho e Fisch, 2007.…”
Section: Materiais E Métodosunclassified